The creation of an Internet public sphere by South Africa's Independent Electoral Commission and Elections Canada - Hannelie Otto; Lynnette Fourie; Johannes Froneman (Communicare)
A prerequisite for a healthy, sustainable democracy is an informed citizenry that participates in the democratic process (see Habermas, 1989:49). In recent years much discourse on the media and democracy correlation has focused on the potential role of the Internet in facilitating political communication by establishing a virtual public sphere. This article investigates the extent to which the South African (IEC) and Canadian electoral commissions’ websites have succeeded in establishing a virtual public sphere. The Elections Canada web site (representing an established democracy) has succeeded better at resembling some of the normative principles of the public sphere theory than has the IEC.